Real-Time Intraoperative MRI Intracerebral Delivery of Induced Pluripotent Stem Cell-Derived Neurons. Issue 4 (April 2017) - Vermilyea, Scott C.; Lu, Jianfeng; Olsen, Miles; Guthrie, Scott; Tao, Yunlong; Fekete, Eva M.; Riedel, Marissa K.; Brunner, Kevin; Boettcher, Carissa; Bondarenko, Viktorya; Brodsky, Ethan; Block, Walter F.; et al.
Induced pluripotent stem cell (iPSC)-derived neurons represent an opportunity for cell replacement strategies for neurodegenerative disorders such as Parkinson's disease (PD). Improvement in cell graft targeting, distribution, and density can be key for disease modification. We have previously developed a trajectory guide system for real-time intraoperative magnetic resonance imaging (RT-IMRI) delivery of infusates, such as viral vector suspensions for gene therapy strategies. Intracerebral delivery of iPSC-derived neurons presents different challenges than viral vectors, including limited cell survival if cells are kept at room temperature for prolonged periods of time, precipitation and aggregation of cells in the cannula, and obstruction during injection, which must be solved for successful application of this delivery approach. To develop procedures suitable for RT-IMRI cell delivery, we first performed in vitro studies to tailor the delivery hardware (e.g., cannula) and defined a range of parameters to be applied (e.g., maximal time span allowable between cell loading in the system and intracerebral injection) to ensure cell survival. Then we performed an in vivo study to evaluate the feasibility of applying the system to nonhuman primates. Our results demonstrate that the RT-IMRI delivery system provides valuable guidance, monitoring, and visualization during intracerebral cell delivery that are compatible with cell survival.